Organizing and Economic Mechanism for Optimization of Industrial Structure in Electric Power Industry of the Republic of Belarus - S. G. Morozov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper reveals economic peculiar features of innovative and investment processes in electric power industry. A scheme of organizing and economic mechanism for optimization of the industrial structure in the Belarusian electric power industry has been given in the paper. Realization of the mechanism will promote to better economic efficiency of power generation in the Belarusian power system and diversification of fuel balance of electric power industry.